Nuclear structure physics: proceedings of the Minerva Symposium on Physics, held at the Weizmann Institute of Science, Rehovot, April 2 - 5, 1973 - Smilansky, Uzy; Talmi, I.; Weidenmüller, Hans-Arwed (Lecture notes in physics, 1973)
Single particle properties of nuclei -- Single-nucleon removal energies -- Effective interactions in nuclei -- Proton, gamma angular correlations near analogue resonances in the mass 90 region -- Analogue resonances - some aspects of reaction mechanism and spectroscopy revisited -- The shape of the fission barrier -- Common aspects in fission and heavy ion reactions -- Determination of nuclear deformations from inelastic scattering of heavy ions near the Coulomb barrier -- Hyperfine interactions in highly ionized atoms -- Measurements of electric quadrupole moments by the pac-technique -- Stopping power effects in nuclear lifetime measurements -- Status of the Darmstadt project -- The new accelerator facility in rehovot -- Some new developments in direct reactions induced by heavy ions
Keywords: Konferenzschrift -- 1973 -- Rehovot; Kernphysik; Kernstruktur